Summary of the 1st Republican Science and Practice Conference "Innovative technologies in education” - Mongush, Svetlana V. (The New Research of Tuva, 2014)
Summary of the 1st Republican Science and Practice Conference "Innovative technologies in education”
Keywords: The 2014 conference; Republican; teaching; innovation